Treatment of wide-necked basilar tip aneurysm not amenable to Y-stenting using the PulseRider device. (23rd July 2015) - Sheth, Sunil A; Patel, Nirav S; Ismail, Ameera F; Freeman, Dena; Duckwiler, Gary; Tateshima, Satoshi
Abstract : Endovascular treatment of broad-necked bifurcation aneurysms remains challenging. Stent-assisted coiling has been successful but requires catheterization of the branches off the parent vessel. We present the case of a patient who failed primary and stent-assisted coiling of a large basilar tip aneurysm because the morphology of the aneurysm precluded successful distal catheterization of the posterior cerebral artery (PCA) branches. Using the PulseRider device, which does not require catheterization of bifurcation branches, we were able to treat the aneurysm successfully.